2008
DOI: 10.2519/jospt.2008.2657
|View full text |Cite
|
Sign up to set email alerts
|

The Timed Up and Go Test for Use on an Inpatient Orthopaedic Rehabilitation Ward

Abstract: There is a need for valid measures to monitor changes in the functional mobility of inpatients of orthopaedic rehabilitation wards. The timed up and go (TUG) test is often used to measure functional mobility 13,24 but it has not been specifically validated for use with the type of complex musculoskeletal conditions seen on an inpatient orthopaedic rehabilitation service.tation because it is simple and easy to administer in a clinical setting. The test consists of measuring the time it takes for an individual t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 32 publications
0
66
0
3
Order By: Relevance
“…28,31,33 The test-retest reliability of the TUG test on inpatients with orthopaedic conditions was found to be 0.80 (ICC 2,2 ). 54 The TUG test has been validated for use with orthopaedic conditions and in a rehabilitation setting. 5,11,22,30,54 For the TUG test, subjects were asked to stand up from a chair, walk with their assistive devices at a comfortable pace to a 3-m marked line, return to the chair, and sit down.…”
Section: Methodsmentioning
confidence: 99%
“…28,31,33 The test-retest reliability of the TUG test on inpatients with orthopaedic conditions was found to be 0.80 (ICC 2,2 ). 54 The TUG test has been validated for use with orthopaedic conditions and in a rehabilitation setting. 5,11,22,30,54 For the TUG test, subjects were asked to stand up from a chair, walk with their assistive devices at a comfortable pace to a 3-m marked line, return to the chair, and sit down.…”
Section: Methodsmentioning
confidence: 99%
“…Para avaliação da presença de comorbidades foi utilizado o índice de Charlson que foi coletado nas primeiras 24 horas 14 . Para realização do cálculo amostral foram utilizados dois estudos prévios como referência, sendo estimado uma correlação de 90% 15,16 , um nível de significância de 5% e uma precisão 10 pontos percentuais, totalizando um tamanho amostral de no mínimo 35 pacientes.…”
Section: Métodosunclassified
“…Brooks et al (2006) reported that the TUG showed large responsiveness to a rehabilitation program that occurred between admission and discharge in a geriatric rehabilitation setting and has moderate to strong correlations with functional ability. Yeung et al (2008) demonstrated that the TUG is a reliable and valid test to assess group change in inpatients on an orthopaedic ward. The TUG has also been shown to be a useful assessment tool as it does not suffer from ceiling or floor effects (Herman et al, 2011).…”
Section: Outcome Measurement: Timed Up and Gomentioning
confidence: 99%
“…Good to strong reliability has also been shown for the individual components of QTUG (McGrath et al, 2011;Greene et al, 2015 andSmith et al, 2015). The standard TUG was also assessed in a group of 142 patients admitted to an orthopaedic rehabilitation unit and was found to be both a reliable and valid outcome measure for use in patients post hip fracture (Yeung et al, 2008). The TUG has also been shown to be a useful assessment tool as it does not suffer from ceiling or floor effects and is sensitive to change (Herman et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation